Supercapitalism the transformation of business, democracy, and everyday life - Reich, Robert B. 1946- (Knopf, 2007)
Offers an analysis of the clash between capitalism and democracy to create a system that has enlarged the economic pie while making democracy less effective, detailing inequities of income and wealth, job insecurity, and the escalating effects of global warming.
Includes bibliographical references and index
Keywords: Democratie; Kapitalisme; Ongelijkheid; Demokratie; Globalisierung; Kapitalismus; Wirtschaftspolitik; Politik; Wirtschaft; Democracy -- Economic aspects -- United States; Capitalism -- Political aspects -- United States; Pressure groups -- United States; Power (Social sciences) -- Economic aspects; Einflussnahme; Unternehmen; USA; United States -- Politics and government; United States -- Economic conditions